The Effect of Media Guidance Motion Picture Education) on Increasing Knowledge of Foot Care for Diabetics Type 2 Mellitus at the Kabila Regency Health Center Bone Bolango - Rifky Ademulya Pou; Zainuddin; Nur Ayun R. Yusuf (Universitas Muhammadiyah Palu, 2026)
he management of DM is still considered underestimated, so disease control is not optimal. Less than optimal management of DMT2 sufferers can cause DMT2 sufferers to experience complications. Neuropathy as a form of microvascular complication plays a role in the appearance of diabetic ulcers. Diabetic ulcers can be prevented and controlled so that they do not develop into more severe through various ways, one of which is by providing education about foot care, as well as doing regular foot care every day. This study aims to determine the effect of motion picture guidance media education on improving foot care knowledge for patients with Type 2 Diabetes Mellitus at the Kabila Health Center, Bone Bolango Regency. This research method uses a type of experimental quasi-research with a one-group pre-post test design with a sample of 56 patients with Type 2 DM at the Kabila Health Center. The analysis technique used the paired sample t test. The results of the study showed that the average value of knowledge level before and after being given education was 47,976. The results of the paired sample t-test obtained a p value of 0.001 < 0.05, it can be said that there is an effect of motion picture guidance media education on improving the knowledge of foot care for patients with type 2 diabetes mellitus with a correlation value of 0.506 (adequate category). The conclusion is that there is an influence of Guidance Motion Picture media education on improving knowledge of foot care for people with type 2 diabetes mellitus at the Kabila Health Center, Bone Bolango Regency.